Case Report: Cerebrovascular Events Associated With Bacterial and SARS-CoV-2 Infections in an Adolescent - de Marcellus, Charles; Dupic, Laurent; Roux, Charles-Joris; El Aouane El Ghomari, Imane; Parize, Perrine; Luscan, Romain; Moulin, Florence; Kossorotoff, Manoelle (Frontiers in Neurology, 2021)
Neurologic manifestations associated with Covid-19 are increasingly reported, especially stroke and acute cerebrovascular events. Beyond cardiovascular risk factors associated with age, some young adults without medical or cardiovascular history had stroke as a presenting feature of Covid-19. Suggested stroke mechanisms in this setting are inflammatory storm, subsequent hypercoagulability, and vasculitis. To date, a handful of pediatric stroke cases associated with Covid-19 have been reported, either with a cardioembolic mechanism or a focal cerebral arteriopathy. We report the case of an adolescent who presented with febrile meningism and stupor. Clinical, biological, and radiological features favored the diagnosis of Lemierre syndrome (LS), with Fusobacterium necrophorum infection (sphenoid sinusitis and meningitis) and intracranial vasculitis. The patient had concurrent SARS-CoV-2 infection. Despite medical and surgical antimicrobial treatment, stroke prevention, and venous thrombosis prevention, he presented with severe cerebrovascular complications. Venous thrombosis and stroke were observed, with an extension of intracranial vasculitis, and lead to death. As both F. necrophorum and SARS-CoV-2 enhance inflammation, coagulation, and activate endothelial cells, we discuss how this coinfection may have potentiated and aggravated the usual course of LS. The potentiation by SARS-CoV-2 of vascular and thrombotic effects of a bacterial infection may represent an underreported cerebrovascular injury mechanism in Covid-19 patients. These findings emphasize the variety of mechanisms underlying stroke in this disease. Moreover, in the setting of SARS-CoV-2 pandemic, we discuss in what extent sanitary measures, namely, lockdown and fear to attend medical facilities, may have delayed diagnosis and influenced outcomes. This case also emphasizes the role of clinical assessment and the limits of telemedicine for acute neurological condition diagnosis.